A Brief Review on Vaginal Drug Delivery in Traditional Persian Medicine - Sayyede Fatemeh Askari; Abdolali Mohagheghzadeh; Amir Azadi; Bahia Namavar Jahromi; Mojgan Tansaz; Parmis Badr (Tehran University of Medical Sciences, 2018)
Based on numerous written works of Persian scholars of Middle ages, Traditional Persian Medicine (TPM) has its own capabilities and strengths. According to TPM, vaginal drug delivery was prioritized to treat gynecological disorders because of the adjacency of uterine and cervix to vagina. This study was carried out to introduce and extract vaginal multi-component dosage forms, suggested by eight key medicinal manuscripts. Traditional terms of abzan, bakhour, fetileh, forzjeh, jalous, hamoul, hoghneh, and shiaf were sought as keywords. More than 670 vaginal formulations had been found for various gynecological disorders such as abortion, amenorrhea, and cervical stenosis. Vaginal dosage forms were categorized based on three physical conditions including solid (forzjeh, fetileh, hamoul, and shiaf), liquid (abzan, jalous, and hoghneh), and gas or smoke (bakhour). More detailed analysis of each vaginal dosage form based on traditional documents is suggested.